Acid-Alkali-Treated Natural Mordenite-Supported Platinum Nanoparticles (Pt/MORn-H-OH) for Efficient Catalytic Oxidation of Formaldehyde at Room Temperature. (3rd April 2019) - Gao, Xiaoya; Guo, Qian; Zhou, Yuan; He, Dedong; Luo, Yongming
Abstract : In this work, a series of natural mordenite-supported platinum (Pt) catalysts were prepared by a facile two-step method, namely, treatment of natural mordenite and then the loading of Pt nanoparticles. The acid-alkali-treated natural mordenite-supported Pt samples (1% Pt/MORn-H-OH) exhibited the highly enhanced catalytic oxidation activity of formaldehyde (HCHO) at room temperature. XRD results showed that the crystalline phase of the mordenite did not change significantly in 1% Pt/MORn-H-OH catalyst. However, the acid-alkali treatment endowed the Pt particles excellent dispersion with the smallest diameter of 2.8 nm in a high loading content, which contributed to the optimal catalytic activity of 1% Pt/MORn-H-OH.